2022
DOI: 10.3390/foods11182862
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Volatile Flavor Compounds, Amino Acids, Organic Acids, and Soluble Sugars in Lemon Juice Vesicles during Freeze-Drying and Hot-Air Drying

Abstract: Lemon juice vesicles have abundant flavor components that can undergo complex changes during drying. Three drying methods, including integrated freeze-drying (IFD), conventional freeze-drying (CFD), and hot-air drying (AD), were studied to determine their effects on the dynamic changes in the flavor compounds in lemon juice vesicles. Compared with the fresh samples, the final dried samples that underwent IFD, CFD, and AD lost seven, seven, and six volatile flavor compounds and three, four, and five amino acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 49 publications
(65 reference statements)
3
13
0
Order By: Relevance
“…In summary, regarding the three drying methods, dried L. decastes via HAD was detected with a higher relative content of aldehydes, alcohols, and ketones than via HAVD and VFD. This was consistent with the research on juice [ 44 , 45 ]. Other than the thermal-treatment effect, this finding could be due to the destruction of the cell wall and cytoplasm via HAD, more various intracellular components released, or the involvement with the reaction during drying [ 16 ]—if considered, more flavor compounds could be produced.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In summary, regarding the three drying methods, dried L. decastes via HAD was detected with a higher relative content of aldehydes, alcohols, and ketones than via HAVD and VFD. This was consistent with the research on juice [ 44 , 45 ]. Other than the thermal-treatment effect, this finding could be due to the destruction of the cell wall and cytoplasm via HAD, more various intracellular components released, or the involvement with the reaction during drying [ 16 ]—if considered, more flavor compounds could be produced.…”
Section: Resultssupporting
confidence: 93%
“…PCA is a multivariate statistical analysis technique. The complex and difficult-to-find variables in the original samples were represented by a few principal component factors, therefore, the differences from the samples could be evaluated according to the contribution rate of principal component factors of the different treatments [ 44 , 45 ]. The PCA of volatile substances in both fresh and different treated L. decastes samples was clarified in Figure 5 .…”
Section: Resultsmentioning
confidence: 99%
“…In our study, lime juice was also a source of amino acids but in lower concentrations than sugars, as also found by Xie et al [ 53 ] in orange, grapefruit, and lemon juice. The metabolomic analysis revealed that the main amino acids in lime juice were asparagine, proline, alanine, glutamine, and 4-aminobutyrate ( Figure 2 B), similar to what was reported in orange and lemon juices [ 54 ].…”
Section: Discussionsupporting
confidence: 86%
“…Lemon juice vesicles are the most important edible tissue in the lemon fruit, accounting for more than 60% of its mass. 4,5 The fresh juice vesicles are extremely sour in taste. It is necessary to process the lemon juice vesicles to increase the economic benefits and flavor qualities of lemon.…”
Section: Introductionmentioning
confidence: 99%
“…4,14,15 However, these volatile compounds are easily transformed and lost during the drying of lemons, which eventually affects the flavor quality of dried lemon products. 5,7 Studies of the metabolic pathways of fruit volatile compounds have mainly focused on the relationship between enzymes and the formation of volatile compounds in fruits, and the key enzymes in the metabolic pathways of volatile compounds, such as lipoxygenase (LOX), alcohol acyltransferase (AAT), and alcohol dehydrogenase (ADH), have become trending research topics. Lipoxygenase is an important rate-limiting enzyme in the initial fatty acid metabolic pathway that converts fatty acids to hydroperoxides, participates in the synthesis of straight-chain esters using fatty acids as precursors, and catalyzes the production of C 6 and C 9 compounds from linoleic and linolenic acids.…”
Section: Introductionmentioning
confidence: 99%